THE STYLISTIC ROLE OF DIALECTS IN M. SHOLOKHOV'S NOVEL "QUIET DON" - Abdullaeva Dilfuza Bobokhanovna (Journals Park Publishing, 2024)
This analysis delves into the intricate use of dialects in M. Sholokhov's "Quiet Don," exploring how linguistic diversity enhances the novel's stylistic depth. The study examines the cultural and narrative implications of various dialects, emphasizing their role in character development, setting authenticity, and overall storytelling.
Keywords: Mikhail Sholokhov, Quiet Don, dialects, stylistic role, linguistic diversity, character development, setting authenticity, Russian Revolution, literary craftsmanship.